Reading for understanding how reading apprenticeship improves disciplinary learning in secondary and college classrooms - Schoenbach, Ruth (Jossey-Bass, 2012)
"A teacher-tested, research-based resource for dramatically improving reading skills. Published in partnership with WestEd, this significantly updated second edition of the bestselling book contains strategies for helping students in middle school through community college gain the reading independence to master subject area textbooks and other material. Based on the Reading Apprenticeship program, which three rigorous "gold standard" research studies have shown to be effective in raising students' reading achievement. Presents a clear framework for improving the reading and subject area learning of all students, including English learners, students with special needs, as well as those in honors and AP courses. Provides concrete tools for classroom use and examples from a range of classrooms. Presents a clear how-to for teachers implementing the subject area literacies of the Common Core Standards. Reading for Understanding proves it's never too late for teachers and students to work together to boost literacy, engagement, and achievement"--